Compilation Successful Grant And Research Proposals - Khalid, Amir (2019)
Writing a successful grant application and research proposal can be one of the most important tasks facing academics, researchers and postgraduate students. “Compilation - Successful Grant and Research Proposals” aim to help readers understand the context within which their proposal will be read, what the reviewers and evaluator panel are looking for and will be influenced the funder policy and budget especially the output research such as commercialization, human capital and publications through the relevant of the flow research and research methodology and practical activities. This book is intended to provide an example of high quality research proposal. Its covers all the multidisciplinary and interdisciplinary research of the successful grant application and research proposal which funded by Malaysia government.  The book lays the successful grant proposal from ScienceFund, Fundamental Research Grant Scheme (FRGS), Exploratory Research Grant Scheme (ERGS) and Research Acculturation Grant Scheme (RAGS). These grant are to carry out the Research and Development projects that can contribute to the discovery of new ideas and the advancement of knowledge in applied sciences. These grant are focusing on development of good quality human capital and encourage the generation of theories, concepts and new ideas that can accelerate new discoveries and innovative creations, high impact and innovative research. Through extensive and annotated successful example and easy-to-understand and easy-to-follow rules and guidelines, this book shows the good example and how to write clearly an interesting research proposal. This book also explaining briefly the way to write the major issues of background of the project, knowledge domain and clarifying why these issues are worthy of attention.  It then proceeds with the concise of the essence of the project presentation and the important of research statement, which can take the form of a hypothesis, a research question, or a goal statement. This book also educated researchers in the critical factors involved in the development of a scientific idea to its successful execution and eventual research proposal.ISBN : 978-967-2306-59-7